Mediation or Moderation? The Role of R&D Investment in the Relationship between Corporate Governance and Firm Performance: Empirical Evidence from the Chinese IT Industry. (9th June 2014) - Zhang, Qing; Chen, Lilin; Feng, Tianjun
Abstract Manuscript Type Empirical Research Question/Issue This paper explores whether R&D investment has a mediating and/or moderating effect on the relationship between corporate governance and firm performance. Research Findings/Insights This empirical study of Chinese IT‐industry listed companies during the 2007–2008 period shows that R&D investment does not moderate, but instead mediates the relationship between corporate governance and firm performance. Theoretical/Academic Implications This paper takes the perspective of technological innovation to empirically examine the effect of corporate governance on firm performance. This study makes a contribution to the literature by showing that technological innovation (i.e., R&D investment) mediates the effects of various governance mechanisms (i.e., ownership concentration, managerial compensation, and asset‐debt ratio) on firm performance. Practitioner/Policy Implications The results provide important managerial implications for the practice of corporate governance in emerging economies. Companies in emerging economies can enhance technological innovation through maintaining relatively high ownership concentration, designing effective managerial compensation systems, and optimizing capital structure. In addition, emerging economies should adopt effective public policies on technological innovation to improve the relationship between corporate governance and firm performance.